ANALYSIS OF THE SUSTAINABILITY REPORTING IN ORDER TO EVALUATE SUSTAINABLE PERFORMANCE AND THE RELATION BETWEEN GETTING AN AWARD IN THE FIELD OF RISK MANAGEMENT OF SUSTAINABILITY IN BANKING SECTOR - Shafara Aulia Shita Ananta; Rob G. Berkhof (Diponegoro Journal of Accounting, 2020)
In recent years, companies have changed their perspective from initially only thinking about profits to developing on the triple bottom concept, which has three important things, namely profit, social, and environment. This concept is also an issue in the implementation of the internal control system in the sustainability side, including the financial sector, particularly in the Bank Industry. This concept also makes Priority Banks in Indonesia begin to be required to report the results of their sustainable performance with sustainability reports. With this new and still developing concept, it is necessary to have a little experience and guidance in Indonesia on the implementation of sustainability reporting which is expected to report sustainable performance to be optimal from an internal control system in terms of sustainable performance at the Bank in Indonesia. This study aims to analyse what factors are agreed in terms of sustainability reporting in terms of optimizing sustainable performance in the Bank Industry. All interpretations of the analysis, findings and conclusions expressed in this thesis aim to provide in-depth information on the Bank Industry in Indonesia and also all other Banks that need further information on this issue about how to optimize sustainable performance with sustainability reports, and the decision to participate in awards on the sustainable side.